2023
DOI: 10.1002/anie.202305127
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Simulation of Controlled Radical Polymerization Forming Dendritic Hyperbranched Polymers

Abstract: Stochastic simulation of the formation process of hyperbranched polymers (HBPs) based on the reversible deactivation radical polymerization (RDRP) using a branch‐inducing monomer, evolmer, has been carried out. The simulation program successfully reproduced the change of dispersities (Đs) during the polymerization process. Furthermore, the simulation suggested that the observed Đs (=1.5–2) are due to the distribution of the number of branches instead of undesired side reactions, and that the branch structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
(7 reference statements)
1
9
0
Order By: Relevance
“…BA [b] (%) The larger Ð value compared to that usually observed in linear polymer synthesis is due to the distribution of the number of branches. [16] All these results support the successful synthesis of HBPBA with a controlled structure. The polymer particle determined by dynamic light scattering (DLS) was reasonably controlled with an average diameter (d) of 143 nm and with a polydispersity index (PDI) of 0.14.…”
Section: Tablesupporting
confidence: 59%
See 1 more Smart Citation
“…BA [b] (%) The larger Ð value compared to that usually observed in linear polymer synthesis is due to the distribution of the number of branches. [16] All these results support the successful synthesis of HBPBA with a controlled structure. The polymer particle determined by dynamic light scattering (DLS) was reasonably controlled with an average diameter (d) of 143 nm and with a polydispersity index (PDI) of 0.14.…”
Section: Tablesupporting
confidence: 59%
“…While the dispersity of the resulting 3 was usually moderate (Ð = 1.5-2), our recent stochastic simulation of the formation process of 3 revealed that the moderate Ðs come from the distribution of the number of branches and that all the polymers have a wellcontrolled branched structure. [16] Furthermore, the (pseudo) generation (G) can be defined like dendrimers. Therefore, this type of HBPs can be named dendritic HBPs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the bioconjugates exhibited a slightly broader molecular weight distribution, arising from the distribution of branching junctions during the copolymerization, a characteristic feature for copolymers with inibramers. 48,49 The copolymerization kinetics were studied to determine the relative rate of incorporation of the inibramer into the branched copolymer grafts. The EY/Cu-catalyzed CRBP was performed using molar ratios of [CBMA]/[SBA]/[CT-iBBr 12 ]/[EYH 2 ]/[CuBr 2 ]/[TPMA] = 200/12/0.08/0.01/0.2/ 0.6.…”
Section: Ct-branched Polymer Conjugatesmentioning
confidence: 99%
“…This inaccuracy in measurement was ascribed to gel formation observed during the synthesis of protein bioconjugates due to excessive radical generation. Furthermore, the bioconjugates exhibited a slightly broader molecular weight distribution, arising from the distribution of branching junctions during the copolymerization, a characteristic feature for copolymers with inibramers. , …”
Section: Synthesis and Characterization Of Ct-branched Polymer Conjug...mentioning
confidence: 99%
“…Alternatively, computer simulations can be conducted, which have been already recognized as an effective tool to probe the reaction kinetics of traditional (nonexchangeable; static) cross-linked systems. Specifically, stochastic kinetic Monte Carlo ( k MC) simulations are capable of simulating the cross-linking process with abundant structural information storage. Such simulations can quantitatively predict the changes of microscopic properties with the extent of reaction under different reaction conditions but can also record the compositional evolution of individual species in an sufficiently large polymer ensemble during cross-linking. , For example, utilizing coupled matrix based Monte Carlo (CMMC), De Smit et al highlighted that reaction conditions for (epoxy-amine-acetoacetate)-based vitrimers need to be optimized to enable a maximization of the number of dynamic groups in a given molecule.…”
Section: Introductionmentioning
confidence: 99%